Peptídeos derivados da peçonha de Bothrops alternatus que interferem na agregação plaquetária - Matias, Mariana Santos (2018)
Cap. II. Snake venoms are considered a library of proteins and peptides that may present important pharmacological actions. In the present work, we analyzed the interference of two synthetic peptides, based on components of the venom of the snake Bothrops alternatus, on hemostasis and its ability to interfere with platelet receptors. Synthetic peptides were named Pep01 and Pep15. The Pep01 was able to affect platelet function by inhibiting platelet aggregation in the presence of collagen. In addition to being able to reduce the mass of a pre-existing blood clot. And the second, demonstrated ability to promote platelet aggregation. These components appear as potential molecules to be used for the development of novel antiaggregant and antithrombotic agents.